Building and sustaining resilient luxury service ecosystems - Taishoff, Marika; Mühlbacher, Hans; Kauppinen-Räisänen, Hannele (Elsevier, 2022)
Research on luxury service ecosystems (LSEs) is in its infancy. LSEs consist of a continuous multiplicity of formally independent yet interdependent actors who align unique and super-modular complementary resources to co-create value with other participants in the system. The purpose of this research is to understand how complex LSEs can be established and made sufficiently resilient to successfully persist in changing or even disruptive contexts over time. A longitudinal analysis of secondary sources and interviews with currently leading actors concerning the development of the LSE of Monaco over a period of nearly 160 years reveals the high importance of joint leadership of a private and a public actor, a strong enduring vision that engages stakeholders, and stable macro-level institutional arrangements that provide a framework for collaborative adaptations and transformation of the ecosystem’s servicescape and service encounters in reaction to ongoing and disruptive changes in the socio-historical context.
Keywords: Service ecosystems; Institutions; Transformative change; Organizational resilience; luxury; fi=Markkinointi|en=Marketing|